2020
DOI: 10.21608/dsu.2020.19585.1015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of the chemotherapeutic effect of thymoquinone loaded on gold nanoparticles through expression of DNA repair enzymes in induced oral squamous cell carcinoma

Abstract: Introduction: Different types of DNA damages occur during the induced oral carcinogenesis, which can be eliminated through several DNA repair pathways. XRCC1 and ERCC1 are the main repair enzymes involved in repair of oral squamous cell carcinoma. A combination of thymoquinone with gold nanoparticles as a novel chemotherapeutic modality is the aim of the present work against chemically induced SCC in the classic model of HBP/DMBA carcinogenesis. Materials and methods: One hundred male Syrian golden hamsters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that TQ impacts the oxidative stress environment of cancer cells, which may contribute to its chemoprevention and cytotoxicity in SCC 5,6,12,16 . As early as 1999, Badary et al investigated the effects of TQ on benzo(a)pyrene (BP)‐induced forestomach squamous cell tumors in mice 12 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that TQ impacts the oxidative stress environment of cancer cells, which may contribute to its chemoprevention and cytotoxicity in SCC 5,6,12,16 . As early as 1999, Badary et al investigated the effects of TQ on benzo(a)pyrene (BP)‐induced forestomach squamous cell tumors in mice 12 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair enzymes such as XRCC1 are therefore integral to mitigating oxidative stress and subsequent carcinogenesis 77 . Amer et al's work in DMBA‐induced buccal pouch SCC in Syrian golden hamsters demonstrated that topical and intraperitoneal injection of TQ‐GNps resulted in cytotoxicity associated with an increase in mRNA and protein expression of XRCC1 5,6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations